Association of lipid lowering drugs and the risk of systemic lupus erythematosus: a drug target Mendelian randomization - Wu, Tong; Ye, Ling; Wang, Shenglan; Huang, Jie; Zhang, Jing (Frontiers in Pharmacology, 2023)
Abstract Background and objective: An interaction between low-density lipoprotein level, lipid-lowering drugs, and systemic lupus erythematosus (SLE) was reported by previous studies. However, whether lipid-lowering drugs provided protective effect for reducing the risk of SLE was unclear. We aimed to clarify this causal relationship through a drug-target Mendelian randomization (MR) study. Methods: Genetic instruments—single nucleotide polymorphism (SNPs)—were utilized to proxy inhibition of the three genes—3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), proprotein convertase subtilisin/kexin type 9 (PCSK9), and Niemann-Pick C1-Like 1(NPC1L1), which was corresponded to three lipid-lowering drugs—statins, evolocumab, and ezetimibe. Low-density lipoprotein (LDL) cholesterol was selected as the biomarker for the measurement of the inhibitors of HMGCR, PCSK9, and NPC1L1, and the genetic data were acquired from the Global Lipids Genetics Consortium, which consisted of 1.3 million participants of European ancestry and 146.5 thousand participants of East Asian ancestry. The genetic dataset of SLE was acquired from two large-scale GWAS studies; one recruited 23,210 participants (7,219 SLE cases and 15,991 controls) of European ancestry and the other one recruited 12,653 participants (4,222 SLE cases and 8,431 controls) of Chinese ancestry. The primary analysis used the inverse variance weighted (IVW) method. Four additional sensitivity analyses, colocalization analysis, and stratification analysis were performed. Results: The primary analysis showed that inhibition of PCSK9 (evolocumab) was associated with a significantly lower risk of SLE (odds ratio [OR] 0.51, 95%CI 0.34 to 0.76, p=0.001) in the European population. The secondary analyses had similar findings. Stratification analysis demonstrated that the preventive effect of PCSK9 inhibition for SLE was similar in both males and females. However, the results were not replicated in the East Asian population. The inhibition of HMGCR (statins) and NPC1L1 (ezetimibe) did not cause a lower risk of SLE. Conclusion: Evolocumab might provide a protective effect on the risk of SLE in the European population, but statins and ezetimibe might not have the protective effect. Further research is necessary to elucidate the specific mechanisms and potential therapeutic applications of PCSK9 inhibitors (evolocumab) in the context of SLE protection. Keyword: lipid lowering drugs, systemic lupus erythematosus, risk, drug target, mendelian randomization